2016
DOI: 10.1002/rrq.152
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Extensive Reading on Reading Comprehension, Reading Rate, and Vocabulary Acquisition

Abstract: Several empirical studies and syntheses of extensive reading have concluded that extensive reading has positive impacts on language learning in second‐ and foreign‐language settings. However, many of the studies contained methodological or curricular limitations, raising questions about the asserted positive effects of extensive reading. The present research adds to the limited set of well‐controlled studies by investigating the impact of an extensive reading approach over a 15‐week semester on the reading com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(136 citation statements)
references
References 23 publications
6
102
0
1
Order By: Relevance
“…Research, with varying degrees of confidence, has reported beneficial effects of ER on various aspects of L2 ability, such as gains in reading speed and reading comprehension (Bell, 2001;He, 2014, Mermestein, 2014Suk, 2017;Tanaka & Stapleton, 2007), silent reading rate (Taguchi, Takayasu-Maass, & Gorsuch 2004), vocabulary knowledge (Tiryaki & Tütüniş, 2012;Wang, 2013), reading comprehension and vocabulary knowledge (Chen, Chen, Chen & Wey, 2013), grammatical competence (Sheu, 2003), and general English language proficiency (Al'zubi, 2014;Elley & Mangubhai, 1983;Yamashita, 2008), and development of writing skill (Al-Mansour & Al-Shorman, 2014;Kirin, 2010;Mermelstein, 2015). The benefits of ER is not limited with linguistic aspects alone, it is also found to boost students' L2 reading motivation (Fujito & Noro, 2009;Guo, 2012), L2 reading attitude (Atay, 2004;Ro & Park, 2016;Salameh, 2017;Yamashita, 2013), L2 reading self-efficacy (Burrows, 2012;Lake, 2014;Raissi & Roustaei, 2013), learner autonomy (Channuan & Wasanasomsithi, 2012;Mede, Incecay, & V. Incecay, 2013) and to lower L2 reading anxiety (Ro, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Research, with varying degrees of confidence, has reported beneficial effects of ER on various aspects of L2 ability, such as gains in reading speed and reading comprehension (Bell, 2001;He, 2014, Mermestein, 2014Suk, 2017;Tanaka & Stapleton, 2007), silent reading rate (Taguchi, Takayasu-Maass, & Gorsuch 2004), vocabulary knowledge (Tiryaki & Tütüniş, 2012;Wang, 2013), reading comprehension and vocabulary knowledge (Chen, Chen, Chen & Wey, 2013), grammatical competence (Sheu, 2003), and general English language proficiency (Al'zubi, 2014;Elley & Mangubhai, 1983;Yamashita, 2008), and development of writing skill (Al-Mansour & Al-Shorman, 2014;Kirin, 2010;Mermelstein, 2015). The benefits of ER is not limited with linguistic aspects alone, it is also found to boost students' L2 reading motivation (Fujito & Noro, 2009;Guo, 2012), L2 reading attitude (Atay, 2004;Ro & Park, 2016;Salameh, 2017;Yamashita, 2013), L2 reading self-efficacy (Burrows, 2012;Lake, 2014;Raissi & Roustaei, 2013), learner autonomy (Channuan & Wasanasomsithi, 2012;Mede, Incecay, & V. Incecay, 2013) and to lower L2 reading anxiety (Ro, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We believe that follow-up activities without too much accountability will not only promote ER per se, but also maximize its benefits when ER is well integrated with other pedagogical practices (see also Day & Bamford, 1998;Jacobs & Farrell, 2012;Suk, 2016). Most importantly, these student reflections clearly show that the combination of ER and ER writing is perceived as an ecological means of improving student writing ability, and is well aligned with the goals of this course on foundational academic ESL writing.…”
Section: Resultsmentioning
confidence: 99%
“…Since the course was TOEIC based General English lessons, it was reasonable to compare their reading and listening skills before and after the course. In addition, extensive reading has been attributed to English learners' vocabulary gain, and increased reading speed and comprehension (Namhee, 2017). Students were assigned to read at least six graded readers during the Fall semester of 2016 and expected to go through them at a pace of one book every two weeks.…”
Section: Methodsmentioning
confidence: 99%